Trends in Water Quality Research: A Bibliometric Study of Factors and Parameters in Drinking Water - Yulia Hasvi Maya Suraya; Didik Dwi Sanyoto; Herawati Herawati; Rosihan Adhani; Lenie Marlinae (Universitas Malahayati Lampung, 2024)
ABSTRACT This study examines trends in water quality research through a bibliometric approach with the aim of mapping dominant factors and parameters and identifying research gaps in this area. The introduction of this research highlights the importance of water quality as a global issue that affects public health and environmental sustainability. The main objective of the study was to analyze water quality-related publications published between 2017 and 2024 using the Publish or Perish application to identify trends, distribution, and research focus. The method used involved collecting data from the 50 highest-ranked journals on Google Scholar, then classifying them by year of publication, publication type, number of citations, and author country. The data obtained was analyzed with the VOSviewer application to generate network visualizations, overlays, and densities to reveal the linkages between research topics. The analysis showed that research on water quality is highly diversified with the main focus on factors affecting water quality and the development of assessment methods. The publications reviewed highlighted global challenges in water quality management and the need for cross-disciplinary collaboration. The conclusions of this study emphasize several research gaps, such as the need for the development of more sensitive water quality indices, the application of new technologies, and further research in local and regional contexts. This research provides valuable insights into current research trends and encourages further exploration to improve water quality management effectively and sustainably. Keywords: Water Quality, Bibliometrics, Assessment Methods, Emerging Technologies, Research Gaps.